Right Sided Intracardiac Thrombosis during Veno-Arterial Extracorporeal Membrane Oxygenation: A Case Report and Literature Review - Bhat, Anusha Ganapati (Case Rep Crit Care, 2019)
Veno-Arterial Extracorporeal Membrane Oxygenation is a common technology of the modern era used as a bridge in severe refractory cardiac and respiratory failure until definitive management is planned. However, early recognition and management of one of the most challenging complications, intracardiac thrombus, continue to remain a conundrum. The incidence of the clinical scenario is very rare. Therefore, due to the lack of literature, there are no guidelines for risk stratification, prevention, or management of intracardiac thrombus. We describe a case of massive pulmonary embolism, who developed a sudden right sided intra-cardiac thrombosis while being optimally anticoagulated on VA ECMO. We also review the literature to describe the pathophysiology, risk stratification, prevention, and management of this rare entity.